Relationship between pH, Eh, and EC with Coconut Production at Different Growing Location - Andreas Izzac Latupapua (Faculty of Agriculture, Pattimura University, 2020)
Three soil chemical properties including pH, Eh, and EC can affect coconut (Cocos nucifera, L.) production. The value of each parameter is usually different from coastal and mountainous soils. This study aims to determine the relationship between pH, Eh, EC and the coconut production of the coastal and mountainous areas. The study method was survey, soil samples were taken at 40 cm depth around the coconut trees, and the number of coconut fruit per tree was observed to determine coconut production. The results showed that the pH, Eh and EC significantly affect the production of the coastal coconuts, while pH significantly affects the production of the mountainous coconuts. The production of the mountainous coconuts reaches 80.4 kg / tree, while the coastal coconuts is 72.4 kg / tree.